POETRY IS FOR PEOPLE (Editors: Tory I. Westermark and Bryan S. Gooch); SIGHTS ANO SOUNDS (Editors: Richard Woollatt and Raymond Souster); MAKING POETRY (Author: Brian S. Powell) - Emery, Winston G. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1974)
Tory I. Westermark and Bryan S. Gooch, eds. POETRY IS FOR PEOPLE. Toronto: Macmillan, 1973. Richard Woollatt and Raymond Souster, eds. SIGHTS ANO SOUNDS. Toronto: Macmillan, 1973. Brian S. Powell. MAKING POETRY. Toronto: Collier Macmillan, 1973. 180 pp. 3.00 (5.95 cloth).